Assessing Farmers’ Impediments in Climate-smart and Non-climate Smart Villages: Kendall’s W Approach - Borah, Abhinab; Lal, Sudhanand Prasad; Singh, K. M.; Prakash, Satya (International Journal of Economic Plants, 2025)
The study was conducted from January-August, 2024 in the Samastipur (Pin code: 848101) and Darbhanga (Pin code: 846001) districts of Bihar. It investigated the constraints faced by farmers in Climate-Smart Villages (CSVs) and non-Climate Smart Villages (non-CSVs) of both Samastipur and Darbhanga districts while adopting Climate-Smart technologies and farming practices in general. Additionally, it aimed to evaluate the level of agreement among farmers regarding the severity of these constraints. A total of 20 constraints were identified and categorised into four broad groups: Technical, Economic and Labour, Social and Personal, and Animals and Pests. Farmers from both CSVs and non-CSVs ranked these constraints on a three-point scale (most severe, severe, not severe), and mean scores were calculated for each constraint. Based on these scores, both individual constraints and broader groups were ranked accordingly. To measure the level of agreement among farmers, Kendall’s coefficient of concordance (W) was applied. The findings revealed that farmers in CSVs exhibited a slightly higher level of agreement (W=0.774) compared to those in non-CSVs (W=0.612), suggesting that CSV interventions may contribute to a more consistent understanding of challenges. These insights are crucial for policymakers and agricultural support systems to design targeted interventions that enhance resilience, sustainability, and overall well-being. Future research should explore how climate-smart interventions shape farmers’ perceptions and long-term agricultural outcomes.